Cellular responses to FGF1 are modulated by palmitoylation of the docking protein FRS2α - Seong J. An; Yoshihisa Suzuki; Jyotidarsini Mohanty; Francisco Tome; Irit Lax; Joseph Schlessinger (Proceedings of the National Academy of Sciences, 2026)
An important mechanism by which receptor tyrosine kinases (RTKs) mediate cellular responses involves the formation of signaling complexes through direct interactions with membrane-associated docking proteins, followed by phosphorylation of multiple tyrosine residues. These docking proteins recruit and activate downstream signaling molecules and enzymes following ligand stimulation. The docking protein FRS2α has been established as a major signaling hub activated by fibroblast growth factors (FGFs), neurotrophic factors, and other extracellular cues. Here, we show that palmitoylation of FRS2α at two sites is essential for stabilizing its myristoylation-dependent association with the plasma membrane. FGF1-induced mitogen-activated protein kinase (MAPK) activation and other cellular responses are partially restored in cells expressing FRS2α mutants deficient in either one of the two palmitoylation sites. However full restoration of signal strength including MAPK response and other FGF1-induced cellular activities requires palmitoylation at both FRS2α sites. In addition to enhancing signaling robustness, anchoring of FRS2α to the plasma membrane creates a structural platform for assembling multiprotein complexes essential for cytoskeletal reorganization associated with membrane ruffling, macropinocytosis, and other FGF1-induced processes. Finally, we demonstrate that while PC12 cells lacking FRS2α or deficient in FRS2α palmitoylation can proliferate, FGF1-induced neuronal differentiation strictly depends on the palmitoylation of the docking protein.